Hubungan Pemakaian Antibiotik dengan Kejadian Infeksi Sectio Caesarea pada Pasien di RSUD Abepura Jayapura Papua - Emma, Nani; Emilia, Ova; Prawitasari, Shinta (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2014)
Background: The number of caesarean section (CS) operations in the world has increased sharply within the last 20 years. Increase of the need for CS operations also increases the problem related to surgical process. Infection happens about 2% to 16% after CS operation. The incidence of post CS is associated with some factors such as supplementation of prophylaxis antibiotics, duration of childbirth, width of membrane wound, duration of surgical nursing monitoring and number of CS. CS infection associated with antibiotic use occurs before or after CS operation. The incidence increases 3 times in patients that do not use antibiotics before CS operation. Use of prophylaxis antibiotics in CS operation significantly minimizes the incidence of infection.Objective: To identify antibiotic use according to standard operational procedure to the incidence of infection in CS mothers.Method: The study was analytical with cross sectional design, undertaken at Abepura Local Hospital. Population were all mothers who gave birth through CS at the hospital. Samples were taken using systematic random sampling technique as many as 44 samples. Data were obtained through questionnaire, interview and document studiesÂ and analyzed using chi square and logistic regression test, risk prevalence at confidence interval (CI) 95% and significance p<0.05.Result: The majority of subject (56.82%) had no infection; 59.09% used antibiotics according to the procedure; 52.27% had good nutrition status; 54.55% had emergency operation; 50% had anemia. Average length of CS operation was 2.26 +1.38 hours. There was significant association between antibiotic use, nutrition status, Hb level, and types of operation and the incidence of CS infection (p<0.05). The result of multivariate analysis showed there was significant association between antibiotic use, nutrition status, types of operation and the incidence of infection. Use of antibiotic brought dominant risk for the incidence of CS infection (PR=2.36; 95% CI=1.45-3.38) whereby antibiotic use, nutrition status and types of operation could predict the incidence of CS infection as much as 10.7%.Conclusion: The majority of subject had no infection and used antibiotic according to the procedure. The probability for the incidence of CS infection was greater in antibiotic use irrelevant with the procedure. Factor most dominantly affecting the incidence of CS infection was antibiotic use irrelevant with the procedure.Â Keywords: antibiotic use, caesarean section, incidence of infection